Agency business cycles - Michail Ju. Golosov; Guido Menzio (Theoretical Economics, 2020)
We develop a theory of endogenous and stochastic fluctuations in economic activity. Individual firms choose to randomize over firing or keeping workers who performed poorly in the past to give them an ex-ante incentive to exert effort. Different firms choose to correlate the outcome of their randomization to reduce the probability with which they fire non-performing workers. Correlated randomization leads to aggregate fluctuations. Aggregate fluctuations are endogenous—they emerge because firms choose to randomize and they choose to randomize in a correlated fashion—and they are stochastic—they are the manifestation of a randomization process. The hallmark of a theory of endogenous and stochastic fluctuations is that the stochastic process for aggregate "shocks" is an equilibrium object.
Keywords: D86; E24; E32; 330; Endogenous and stochastic cycles; coordinated randomization; unemployment fluctuations